Seepage Behavior of Earth Dams Considering Rainfall Effects - Jong-Wook Lee; Jiseong Kim; Gi-Chun Kang (Advances in Civil Engineering)
More than 60% of annual rainfall in Korea is concentrated during the monsoon season from June to August because of the climate characteristics of East Asia. In general, reservoir water levels sharply rise during this period and rock-fill dams are exposed to various types of damages such as soil erosion and piping related to seepage problems. However, the detection of seepage problems is generally more difficult because rainfall directly flows into a V-notch weir according to a downstream shell in which seepage rates can be measured downstream. In this paper, rainfall is filtered out from the measured seepage rates to evaluate the effects of rainfall by using a digital filtering method for two large rock-fill dams (Dams A and B). Seepage behavior for these two large rock-fill dams was estimated as a steady-state condition. It has been proven that with the application of a digital filter which filters out rainfall-induced infiltration into a downstream shell from a measured seepage flow would make analyzing the seepage behavior of dams more effective. This also shows that consideration for any rainfall effect on the seepage behavior of earth dams is very important. The seepage rate of Dam A was not significantly affected by rainfall because the seepage water was collected inside the dam body and was transferred to a V-notch weir located downstream from the dam through a steel pipe. On the contrary, the seepage rate of Dam B was greatly influenced by rainfall in the rainy season. Also, the permeability of the core zones for Dams A and B was estimated at 8.5 × 10−5 cm/sec and 2.7 × 10−5 cm/sec, respectively, by a simplified method.